Pengambilan Keputusan untuk Menentukan Strategi dalam Promosi Menarik Minat Siswa Baru Menggunakan Metode Waspas: (Studi Kasus: SMP-IT Mutia Rahma) - Arisma Yulistiani; Yani Maulita; Suria Alamsyah (Switch : Jurnal Sains dan Teknologi Informasi, 2024)
Promotion is an element used to inform and persuade the market about new products or services at the company through advertising, personal sales, sales promotions, or publications. However, due to the large selection of promotional media nowadays, agencies are required to continue to make decisions well, precisely and quickly, and to be accountable in making decisions. SMP-IT Mutia Rahma is one of the private schools in the Tanjung Perak sub-district. Until now, promotional activities for student admissions have only been carried out by visiting promotional destinations, such as putting up banners in public places, as well as distributing brochures to the public to help with activities. promotion. The method currently used is still considered very slow in disseminating information regarding promotion strategies for new student admissions, apart from that, this method also requires very large costs to increase promotional media, such as brochures and banners. The school should be able to see opportunities to promote promotional activities on social media. In addition, in the last two years there has been a decline in the number of students registering.